Exceptional rates and mechanisms of muddy shoreline retreat following mangrove removal. Issue 8 (4th March 2019) - Brunier, Guillaume; Anthony, Edward J.; Gratiot, Nicolas; Gardel, Antoine
Abstract: Probably the largest regular shoreline fluctuations on Earth occur along the 1500 km‐long wave‐exposed Guianas coast of South America between the mouths of the Amazon and Orinoco Rivers, the world's longest muddy coast. The Guianas coast is influenced by a succession of mud banks migrating northwestward from the Amazon. Migrating mud banks dissipate waves, partially weld onshore, and lead to coastal progradation, aided by large‐scale colonization by mangroves, whereas mangrove‐colonized areas between banks (inter‐bank areas) are exposed to strong wave action and undergo erosion. On large tracts of this coast, urbanization and farming have led to fragmentation and removal of mangroves, resulting in aggravated shoreline retreat. To highlight this situation, we determined, in a setting where mangroves and backshore freshwater marshes have been converted into rice polders in French Guiana, shoreline change over 38 years (1976‐2014) from satellite images and aerial orthophotographs. We also conducted four field experiments between October 2013 and October 2014, comprising topographic and hydrodynamic measurements, to determine mechanisms of retreat. The polder showed persistent retreat, at peak rates of up to ‐200 m/yr, and no recovery over the 38‐year period of monitored change. Notwithstanding high erosion rates, mangrove shorelines show strong resilience, with recovery characterized by massive accretion. Retreat of the polder results in a steep wave‐reworked shoreface with a lowered capacity for bank welding onshore and mangrove establishment. Persistent polder erosion is accompanied by the formation of a sandy chenier that retreats landwards at rates largely exceeding those in inter‐bank situations. These results show that anthropogenic mangrove removal can durably modify the morphodynamics of muddy shorefaces. This limits the capacity for shoreline recovery and mangrove re‐establishment even when there is no sustained long‐term deficit in mud supply, as in the case of the Amazon‐influenced Guianas coast. © 2019 John Wiley & Sons, Ltd. Abstract : Mangrove removal for agriculture and urbanization on the 1500 km‐long Amazon‐influenced wave‐exposed Guianas coast is resulting in aggravated shoreline retreat. Remote sensing and field experiments show that mangrove removal results in a low, steep and persistently retreating shoreface that precludes large‐scale mud‐bank sedimentation and subsequent mangrove recolonization, while favouring active sandy chenier formation. Development planning on this extremely dynamic muddy coast needs to be considered in terms of space‐ and time‐varying mud‐bank and inter‐bank phases and preservation of mangroves.